2017
DOI: 10.1186/s13568-017-0375-4
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment methods of lignocellulosic biomass for anaerobic digestion

Abstract: Agricultural residues, such as lignocellulosic materials (LM), are the most attractive renewable bioenergy sources and are abundantly found in nature. Anaerobic digestion has been extensively studied for the effective utilization of LM for biogas production. Experimental investigation of physiochemical changes that occur during pretreatment is needed for developing mechanistic and effective models that can be employed for the rational design of pretreatment processes. Various-cutting edge pretreatment technolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
150
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 371 publications
(186 citation statements)
references
References 63 publications
1
150
0
4
Order By: Relevance
“…The common pretreatment methods routinely used for degradation of LB are broadly classified into physical, chemical, physicochemical, biological, biochemical, and multiple or combinatorial pretreatment methods. Various comprehensive reviews have been published emphasizing conventional pretreatment methods and their mechanical effects on plant cell walls . These methods are therefore discussed briefly in the present review.…”
Section: Conventional Pretreatment Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The common pretreatment methods routinely used for degradation of LB are broadly classified into physical, chemical, physicochemical, biological, biochemical, and multiple or combinatorial pretreatment methods. Various comprehensive reviews have been published emphasizing conventional pretreatment methods and their mechanical effects on plant cell walls . These methods are therefore discussed briefly in the present review.…”
Section: Conventional Pretreatment Methodsmentioning
confidence: 99%
“…Currently, more emphasis is being given to the search for the cheapest raw materials during the production of second‐generation (2G) biofuels / biochemicals. Research later established that different feedstocks using lignocellulosic biomass (LB) such as wheat and sugarcane straws, rice husk, sugarcane bagasse, forest and agricultural residues, industrial and urban waste, could serve as ideal sources for the production of 2G biofuel (bioethanol) …”
Section: Introductionmentioning
confidence: 99%
“…This suggests that there are temperature-related factors that negatively affect the Ym at higher temperatures. Thermochemical hydrolysis of lignocellulosic biomass produces different types of inhibitory substances [6]. Hemicellulose sugars may be converted to inhibitory forms, such as furfural and hydroxymethyl-furfural, particularly at high temperatures [20,21].…”
Section: Correlation Between Sd and Ymmentioning
confidence: 99%
“…Pretreatment methods using biological, mechanical, chemical, and thermal means and their combinations have been applied to improve the degradability of lignocellulosic biomass [6]. Thermochemical pretreatment is considered a highly effective method because of low time, resource, and energy requirements [7].…”
Section: Introductionmentioning
confidence: 99%
“…Lignin is one of the three main components of plants, along with cellulose and hemicellulose, and is the most abundant renewable aromatic polymer on earth (Saeed et al 2012;Amin et al 2017;MacLellan et al 2017). Many studies have shown that lignin is a biomolecular polymer that consists of three main benzoyl propane structural units (syringyl (S), guaiacyl (G), and p-hydroxyphenyl (H)) linked by a variety of carbon-carbon and carbon-oxygen bonds (Boeriu et al 2004;Feofilova and Mysyakina 2016;Xie et al 2017).…”
Section: Introductionmentioning
confidence: 99%